Innovation Strategy Based on Industry 4.0 and Digital Transformation in SME Companies in Iran - Adel Sepehr; Manouchehr Manteghi; Vahid Baradaran (International Journal of Digital Content Management, 2023)
Small and medium enterprises (SMEs) have become a vital factor for national competitiveness and firms and companies, and the world is increasingly moving towards a knowledge-based economy. Innovation and technological changes are strongly influenced by the country/place where they occur. The main purpose of this study is to present the framework of SME innovation strategy with the approach of the fourth generation industry in Iran, which has been done using the GT method i.e a blend of qualitative and quantitative methods. The research population includes small and medium businesses and industrial townships in Tehran. The method of data collection in the qualitative part is the interview and in the quantitative part a questionnaire. The findings show that the innovation strategy framework in SME in the fourth industrial revolution is one of the causal factors with 5 components including small and medium businesses, organization maturity model, digitization, rules and regulations and innovation strategy. The results consist of 8 sub-components, which can be enumerated as market development, increasing exports, increasing productivity, creating added value, improving financial credits, training work managers, entrepreneurship and finally creating employment. The results show that the program factors have an effect on the facilitating factors; the causal factors on the innovation framework; the informational factors on the obstacles; supervisory and control factors on facilitating factors; barriers on the innovation framework; ; Financial resources have an effect on obstacles, consequences on innovation framework and structural factors on obstacles in small and medium enterprises. In our country, despite the fact that more than 59% of all production units are included in the EMS small and medium industries group,  these companies have not gained a significant share in the national gross product and creating added value and are suffering from severe shortages. While small and medium-sized companies can move away from the traditional focus on the product and take steps in the development of product innovation by using the fourth generation industry and new technology, creating a strategy and coming up with new products and services  will create more added value; The formulation of the strategy for any organization calls for an innovative point of view .